Boiogito, a Kampo medicine, improves hydrarthrosis in a rat model of knee osteoarthritis. Issue 1 (December 2015) - Fujitsuka, Naoki; Tamai, Mitsuo; Tsuchiya, Kazuaki; Iizuka, Seiichi; Tsuchiya, Naoko; Makino, Bunsho; Hattori, Tomohisa; Kase, Yoshio; Isohama, Yoichiro
Abstract Background Hydrarthrosis, which is associated with knee pain and limited range of motion, decreases the quality of life (QOL) of patients with osteoarthritis (OA). The Kampo medicine boiogito is prescribed for the treatment of knee OA with hydrarthrosis; however, its precise mechanisms of action remain unknown. The purposes of this study were to assess the pharmacological effects of boiogito and its mechanisms of action on joint effusion in rats with surgically induced OA. Methods A rat OA model was produced by transecting the anterior (cranial) cruciate ligament, medial collateral ligament, and medial meniscus in the right knee joints of 7-week-old female Wistar rats. The rats were given chow containing boiogito (1 or 2 %) or indomethacin (0.002 %) for 4 weeks after surgical transection. Levels of interleukin-1β (IL-1β) and hyaluronic acid (HA) were measured by enzyme-linked immunosorbent assay. Knee joint pain was assessed using an incapacitance tester. Osmotic water permeability in cultured rabbit synovial cells was assessed using stopped-flow analysis. Results Increased synovial fluid volume and knee joint pain were observed in rats with surgically induced OA. In rats with OA, levels of IL-1β and HA in the articular cavity were higher but concentration of HA in synovial fluid was lower than in sham-operated rats, suggesting excessive synovial fluid secretion. Administration of boiogito improved hydrarthrosis, IL-1β, and HA concentrations and alleviated knee joint pain in rats with OA. Indomethacin reduced IL-1β and knee joint pain but failed to improve hydrarthrosis or HA concentration in rats with OA. Osmotic water permeability in synovial cells, which is related to the function of the water channel aquaporin, was decreased by treatment with boiogito. Conclusion Boiogito ameliorates the increased knee joint effusion in rats with OA by suppressing pro-inflammatory cytokine IL-1β production in the articular cavity and regulating function of water transport in the synovium. The improvement of hydrarthrosis by boiogito results in the increased HA concentration in synovial fluid, thus reducing joint pain. Boiogito may be a clinically useful treatment of QOL in patients with OA with hydrarthrosis.